Case report and literature review: Asymptomatic littoral cell angioma in a 3-year-old girl - Mou, Yanling; Yang, Liucheng; Wang, Jianjun; Chen, Qinming; Zhang, Mengzhen; Zhang, Xi; Tan, Rongying; Adam Mahamat, Djibril; Wu, Kai (Frontiers in Pediatrics, 2024)
Littoral Cell Angioma (LCA) is an extremely uncommon benign vascular tumor of the spleen.Cases of the LCA in infants are rarely reported, and due to the rarity of the tumor and nonspecific symptoms, diagnosis of LCA is often overlooked in clinical practice.We present a three-year-old girl with pulmonary inflammatory who was admitted to the hospital due to the discovery of a space-occupying lesion in the spleen. Pathology after splenectomy confirmed LCA, and there was no recurrence observed during five-month follow-up examination after surgery.LCA should be considered when a child shows asymptomatic splenomegaly, with antigen expression indicating dual positive of endothelial and histiocytic markers. Laparoscopic splenectomy remains the primary method of treating LCA.